PEMBERDAYAAN KELOMPOK TANI “TANI BERSAMA” MELALUI TEKNOLOGI BUDIDAYA JAHE MERAH (Zingiber officinale) DI PADANG LUAS KECAMATAN KURAU - Zulipah Mahdalena; Muhammad Agung Wahyudi (Fakultas Pertanian UVAYA Banjarmasin, 2024)
Red ginger is a pant that is benefits and has high economic value. Red ginger is very beneficial for health and is usually used as raw material for the traditional medicine industry, and can also be processed into drinks or as a cooking spice. Now yuo can find many processed instant red ginger products that are ready to be brewed. The technology for cultivating red ginger in Padang luas village is one of the efforts to empower the farming community to have knowledge,skills and insight other than cultivating lowland rice and is expected to increasefarmers income. Red ginger is very popular and continues to experience increasing demand,however this demand cannot be fully met, so the price tends to be expensive. From this activity, it is hoped that farmers can apply the knowledge they have can omprove farmer welfare. This coommunity service activity uses a persuasive approach with direct interview techniques to identify problems. The activity stage includes location survey,activity implementation, and evaluation.The service activity was carried out on 15 to 16 Mei 2024, at one of the farmer group members homes and was attended by approximately 20 farmer group members and women around the location. The Result of the community service activities to empower the farmer group “Tani Bersama” through Red ginger cultivation technology in polybags have had a positive impact on the farmer group, namely by increasing knowledge, skills and insight regarding Red ginger cultivation technology. In general, farmer groups are very responsive and welcome the comunity service activities provided